Visual Outcomes of Secondary Lens Implants in Children with Different Etiologies - Shah, Shreya; Shah, Mehul; Kataria, Apeksha; Korane, Ashvini (Journal of Ophthalmology and Research, 2022)
This study investigated visual outcomes and factors that impact vision in children receiving secondary intraocular lens (IOL) implants.